2011
DOI: 10.1007/s10745-011-9397-8
|View full text |Cite
|
Sign up to set email alerts
|

Last Trip Return Rate Influence Patch Choice Decisions of Small-Scale Shrimp Trawlers: Optimal Foraging in São Francisco, Coastal Brazil

Abstract: Studies using Optimal Foraging Theory to understand human behavior have stated that daily variation in patch profitability could explain mismatches between theoretical predictions and actual behavior. In this paper, we tested whether the return rate of the last fishing trip could predict fishers' choices to return or choose a different fishing ground for their next trip. We collected data on fishing trips using interviews and direct observation of fishers' activities at the main landing point in São Francisco,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…This research shows that a higher fishing effort correlates with a higher CPUE, consistent with the predictions of optimal foraging theories and patch time allocation models (Sosis 2002;Chimello de Oliveira and Begossi 2011;Aswani 1998;Thomas 2007). However, further analysis of individual differentiation over the same space reveals that the same set of individuals habitually harvest less productive areas as spaces they have claimed as "their own."…”
Section: Becoming Enseñado: the Social Production Of Fishing Spacesupporting
confidence: 81%
See 1 more Smart Citation
“…This research shows that a higher fishing effort correlates with a higher CPUE, consistent with the predictions of optimal foraging theories and patch time allocation models (Sosis 2002;Chimello de Oliveira and Begossi 2011;Aswani 1998;Thomas 2007). However, further analysis of individual differentiation over the same space reveals that the same set of individuals habitually harvest less productive areas as spaces they have claimed as "their own."…”
Section: Becoming Enseñado: the Social Production Of Fishing Spacesupporting
confidence: 81%
“…They move on to the next most profitable patch when the returns fall below the average. As predicted by optimal foraging theory, fishers alternate fishing grounds based on their knowledge and experience with patch productivity on a previous day (Sosis 2002;Chimello de Oliveira and Begossi 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This decline in high valued species was not observed in the southeastern Brazilian coast over the studied timeframe, which further indicated that fishing pressure had not reached critical levels. On the contrary, high valued species were more often mentioned in recent interviews, possibly related to increased exploitation of shrimps and large reef predators, such as groupers and snappers (Lutjanidae) [11,15,41,52]. Other possibility would be that the relative value of these fishing resources increased over time, so fishers interviewed more recently may be applying a more intense fishing effort to catch these fishing resources.…”
Section: Temporal Trends In Catch Abundance and Compositionmentioning
confidence: 99%
“…For example, Lopes and Begossi (2011) found that the number of trips on a given day was positively correlated with catch on the previous day for small-scale trawlers, while de Olivera and Begossi (2011) found that the return rate on the last fishing trip influenced fishers' choices to return to that fishing ground on their next trip. Following an unprofitable trip, skippers will often remain in port to avoid further losses, typically until conditions affecting the perceived availability of fish (e.g.…”
Section: Social Riskmentioning
confidence: 99%